2021
DOI: 10.1108/bfj-04-2021-0409
|View full text |Cite
|
Sign up to set email alerts
|

Serbian, Croatian and Spanish consumers' beliefs towards artisan cheese

Abstract: PurposeIn the past two decades the popularity of artisan cheese emerged. The present study aimed to investigate similarities and differences in beliefs towards artisan cheeses among participants from Serbia, Croatia and Spain and to determine consumer profiles. Better understanding of their behaviours and beliefs could serve as the basis for the development of appropriate production and marketing strategies and for further popularisation of artisan cheeses.Design/methodology/approachThe data on demographic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…In this study, participants in cluster 2 ("Unconcerned consumers") came mostly from Croatia, Serbia and Slovenia, holding food traditions and loyalty to local shops and open markets in high regard . This is in line with a study by Miloradovic et al (2021), where greater percentage of consumers from Serbia and Croatia purchased artisan cheeses at the open markets compared to Spanish consumers. Nevertheless, some of these markets with a wide variety of foods are regarded as high-risk for dairy, meat and fish products (Sirsat et al 2015).…”
Section: Attitudes Towards Chilled Rte Foodssupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, participants in cluster 2 ("Unconcerned consumers") came mostly from Croatia, Serbia and Slovenia, holding food traditions and loyalty to local shops and open markets in high regard . This is in line with a study by Miloradovic et al (2021), where greater percentage of consumers from Serbia and Croatia purchased artisan cheeses at the open markets compared to Spanish consumers. Nevertheless, some of these markets with a wide variety of foods are regarded as high-risk for dairy, meat and fish products (Sirsat et al 2015).…”
Section: Attitudes Towards Chilled Rte Foodssupporting
confidence: 91%
“…The clustering solution is considered poor when the silhouette measure is < 0.20, values of > 0.50 indicate a good and intermediate values an acceptable clustering solution (Mooi and Sarstedt 2011). Two-step cluster analysis is considered to be more accurate and reliable compared to other clustering methods and was extensively used in different fields (Tkaczynski 2016) and in numerous consumer studies (Geeroms et al 2008;Miloradovic et al 2021;Zakowska-Biemans 2011;Zhllima et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al (2021) observed that low‐risk Southern Brazil consumers associates open market dairy product consumption to know the product and believed in the seller. Croatian, Serbian and Spanish consumers have reported to value more artisan cheeses over industrial ones in terms of quality, although they believe that packaging and labeling need improvement (Miloradovic et al, 2022). Lahne and Trubek (2014) suggested that consumers combine information about producer practice, social context, and the materiality of the product through an active, learned practice of sensory perception.…”
Section: Resultsmentioning
confidence: 99%
“…to relate the sample to the other stimuli rates were close to "I moderately liked" (average rate between 7.2 and 7.3). (Miloradovic et al, 2022). Lahne and Trubek (2014) suggested that consumers combine information about producer practice, social context, and the materiality of the product through an active, learned practice of sensory perception.…”
Section: Resultsmentioning
confidence: 99%
“…It is obvious that regardless of flexibility of safety and quality legal requirements, small scale produced whey from the Serbian market does not have any quality shortage compared to the large scale produced whey. It is clear that this branch represents an undeniable potential to be supported and promoted, especially bearing in mind that in Serbia, consumers perceive small scale foods as superior from the aspects of both health and quality, compared to their large scale counterparts (Miloradovic et al, 2021).…”
Section: Comparison Of the Quality Of Small And Large Scale Market Wheymentioning
confidence: 99%